Sustainable open innovation for ammunition waste management: Proposal for implementation in brazilian public security institutions (Research, Society and Development, 2024)
The study describes how looking at collaborative processes with a sustainable bias can effectively contribute, through sustainable open innovation, to opportunities for solving challenges of the same context. Therefore, we present a study proposal to improve the public security arena (reverse logistics of ammunition expended in training), aiming at recycling the generated waste. The research strategy was case study analysis, which is appropriate for investigating real-life events. It was necessary to understand which factors contribute to qualifying the requirements for reverse logistics and sustainable innovation in public security institutions. The specific objective is to link the maturity level of the public security institutions to its goals in reverse logistics, to give greater view to implement it. As a result, we were able to increase the current status of knowledge regarding the sustainable disposal of expended ammunition cases and get a better understanding of the economic gains by selling the brass scraps waste (expended ammunition) as a large expected benefit, collaborating to reduce the customer’s costs by enhancing their reverse logistics processes. Also, considering the solutions to complex problems through collaboration, knowledge of purposes, and organizational maturity, point out the relationship between sustainability and innovation.